The vegetative propagation of some commercial deciduous fruit tree varieties and rootstocks with special reference to cuttings - Du Preez, D (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1931.